A class of Hamilton–Jacobi equations on Banach–Finsler manifolds. (January 2015) - Jaramillo, J.A.; Jiménez-Sevilla, M.; Ródenas-Pedregosa, J.L.; Sánchez-González, L.
Abstract: The concept of subdifferentiability is studied in the context of C 1 Finsler manifolds (modeled on a Banach space with a Lipschitz C 1 bump function). A class of Hamilton–Jacobi equations defined on C 1 Finsler manifolds is studied and several results related to the existence and uniqueness of viscosity solutions are obtained.